Dibenzothienopyrrolo[3, 2‐b]pyrrole: The Missing Member of the Thienoacene Family. Issue 4 (5th February 2018) - Tasior, Mariusz; Czichy, Małgorzata; Łapkowski, Mieczysław; Gryko, Daniel T.
Abstract: Dibenzothienopyrrolo[3, 2‐ b ]pyrrole and the corresponding bis( S, S ‐dioxide) were synthesized by using a concise synthetic strategy. Despite the presence of six fused aromatic rings, π‐expanded pyrrolo[3, 2‐ b ]pyrroles of this type absorb and emit at relatively short wavelengths, which reflects inefficient π conjugation due to the angular arrangement of the aromatic rings. They exhibit interesting and complex electrochemical behavior, which highlights their potential in organic electronics. Both heteroacenes undergo two‐stage oxidation while retaining the independence of each 1‐phenyl‐1 H ‐[1]benzothieno[3, 2‐ b ]pyrrole, which was proved by in situ electron spin resonance measurements. Interestingly, electrochemically generated dicationdiradicals are not only distributed over the pyrrolo[3, 2‐ b ]pyrrole scaffold, but also over the phenyl substituents located on nitrogen atoms. Abstract : Here it is, finally : Dibenzothienopyrrolo[3, 2‐ b ]pyrrole, and its S, S, S ′, S ′‐tetraoxide, were synthesized for the first time (see scheme; TFA=trifluoroacetic acid, TBAF=tetrabutylammonium fluoride, DCM=dichloromethane, mCPBA= m ‐chloroperbenzoic acid) and their physicochemical properties have been studied. Electrochemically generated dication diradicals are not only distributed on the heterocyclic core, but also over the phenyl substituents on the nitrogen atoms.